Трифазно-однофазний асинхронний електропривод з багатоелементним ємнісним фазозміщуючим модулем - Шуруб, Ю.В. (Електротехніка і електромеханіка, 2011)
A circuit design of a three-one phase induction electric drive with a three-element phase-shifting module is introduced to provide symmetrical conditions in a wide load range.